Improved poetry writing skills through inductive model word pictures (pwim) in grade v elementary school students of Pasiraman Lor district Banyumas in the school year 2018/2019 - Mohamad Yusuf Kandahlawy; Hartono Hartono; Sularmi Sularmi (Universitas Sebelas Maret, 2021)
Abstract. This research aims to upgrade Poetry Writing Skills through Picture Word Inductive Model (PWIM) in Grade V of State Elementary School Pasiraman Lor in the academic year 2018/2019. This research motivated by low poetry writing skills. This study will be held in 2 cycles, each cycle consist of 3 meetings, namely the planning, implementation, and reflection stages. The students of V grade that consist of 6 female and 10 male students are the subject of this research. Data collection methods are interviews, observation, documentation, and tests. The validity used is technical and source triangulation. Data analysis shows qualitative descriptive data analysis. The aspects assessed in writing poetry are the novelty’s theme and meaning, the power of imagination, the accuracy of diction, the exposures of exposition, and the teacher's affective response. As the results, the percentage of completeness of students' poetry writing skills was pre-action 23.53%, cycle I 58.82%, and cycle II 88.24%.The conclusion of this study is that poetry writing skills can be improve by using PWMI. Keywords: poetry writing skills, Picture Word Inductive Model (PWIM), quality of learning outcomes, elementary school